Using Here, Hidden, and in My Head (3H) Strategy to Improve Students’ Reading Comprehension of the Eleventh Grade of SMK Negeri 1 Jarai - Iqbal Pandutama; Sri Wahyuni; Yoga Pratama (JEIT (Journal of Educational Innovations and Technologies), 2025)
This study aimed to determine the significant difference in students’ reading comprehension between those taught using the Here, Hidden, and In My Head (3H) strategy and those who were not. The research population comprised 186 eleventh-grade students at SMK Negeri 1 Jarai. The sample consisted of an experimental class (n=25) and a control class (n=25), they were selected through purposive sampling. This quasi-experimental study used a reading test for data collection, analyzed using SPSS version 25. The pre-test and post-test results, along with paired and independent sample t-tests, revealed that the t-obtained value was 3.497 at a significance level of p<0.005 (two-tailed) with a degree of freedom (df) = 48, exceeding the t-table critical value of 1.677. Since the t-obtained was higher than the t-table, it was concluded that the 3H strategy significantly improved students' reading comprehension. Thus, implementing the 3H strategy effectively enhances students' reading comprehension skills. Future researchers are recommended to explore the long-term effects of the 3H strategy, apply it to different educational levels, and integrate it with other instructional approaches to maximize its impact on reading comprehension.